2003
DOI: 10.1128/aem.69.6.3636-3639.2003
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reduction and Precipitation of Vanadium by Shewanella oneidensis

Abstract: Shewanella oneidensis couples anaerobic oxidation of lactate, formate, and pyruvate to the reduction of vanadium pentoxide (V V ). The bacterium reduces V V (vanadate ion) to V IV (vanadyl ion) in an anaerobic atmosphere. The resulting vanadyl ion precipitates as a V IV -containing solid.Vanadium is a transition metal which, at neutral pH, can exist in two oxidation states, V IV (vanadyl ion, cationic species VO 2ϩ ), and V V (vanadate ion, anionic species, H 2 VO 4 Ϫ ) (10, 11).The environmental chemistry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 12 publications
2
99
0
Order By: Relevance
“…In addition to the catalytic NrfA subunit, NRF consists of a pentahaem cytochrome c (NrfB), an ironsulfur cluster protein on the periplasmic face of the membrane (NrfC) and a transmembrane domain (NrfD), which as the NrfABCD cluster is commonly found in cproteobacteria Hussain et al, 1994;Simon et al, 2000). The NapC homologue, CymA, has been found to be essential in S. oneidensis MR-1 for the anaerobic reduction of nitrate, nitrite, Fe(III), Mn(IV), DMSO or V(V) (Carpentier et al, 2005;Gao et al, 2009;Myers & Myers, 1997, 2000Schwalb et al, 2003). Putative CymA proteins with 68.1 % identity are encoded in the genomes of all Shewanella species that encode NAP-b.…”
Section: Protein Pool Subunitmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the catalytic NrfA subunit, NRF consists of a pentahaem cytochrome c (NrfB), an ironsulfur cluster protein on the periplasmic face of the membrane (NrfC) and a transmembrane domain (NrfD), which as the NrfABCD cluster is commonly found in cproteobacteria Hussain et al, 1994;Simon et al, 2000). The NapC homologue, CymA, has been found to be essential in S. oneidensis MR-1 for the anaerobic reduction of nitrate, nitrite, Fe(III), Mn(IV), DMSO or V(V) (Carpentier et al, 2005;Gao et al, 2009;Myers & Myers, 1997, 2000Schwalb et al, 2003). Putative CymA proteins with 68.1 % identity are encoded in the genomes of all Shewanella species that encode NAP-b.…”
Section: Protein Pool Subunitmentioning
confidence: 99%
“…nov. have been characterized from marine environments (Bozal et al, 2009;Park et al, 2009) and contribute to the 51 species of Shewanella identified at the time of writing (http://www.bacterio.cict.fr/). Some Shewanella species, most notably Shewanella oneidensis MR-1, can grow via the reduction of metal oxides -including Fe(III), Mn(IV), Cr(VI), U(VI), Tc(VI), V(V) -thiosulfate, elemental sulfur and arsenate (Burns & DiChristina, 2009;Carpentier et al, 2005;Konstantinidis et al, 2009;Malasarn et al, 2008;Murphy & Saltikov, 2007;Nealson & Saffarini, 1994;Nealson & Little, 1997). The respiratory versatility of Shewanella species has significant implications in bioremediation and in the assembly of microbial fuel cells (Fredrickson et al, 2008;Hou et al, 2009;Kim et al, 2002;Tiedje, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic microorganisms enzymatically reduce contaminant metals such as uranium, chromium, technetium, vanadium and metalloids such as selenium thereby converting these metals to less soluble forms Lovley & Coates 2000;Carpentier et al 2003;Ortiz-Bernard et al 2004). Stimulation of metal reduction within the subsurface offers a relatively simple method to remove metal contaminants from groundwater, thereby limiting or greatly reducing further transport of contaminants downgradient (Lovley et al 1991;Lovley 1993;.…”
Section: Metal Remediation Through Biodegradation Of Associated Organmentioning
confidence: 99%
“…Vanadium can exist in oxidation states ranging from 22 to +5, though at neutral pH vanadium commonly exists as V(V) (vanadate) and V(IV) (vanadyl), of which the former is the most toxic and mobile form (Ortiz-Bernad et al, 2004). Vanadium(V)-reducing microbes that have been reported to date include species of the genus Pseudomonas (Lyalkova & Yurkova, 1992) and the metal-reducing organisms Shewanella oneidensis (Carpentier et al, 2003) and Geobacter metallireducens (Ortiz-Bernad et al, 2004). In this paper, we describe a strictly anaerobic, thermophilic bacterium designated strain VF08 T , which reduces vanadium(V) and represents a novel species of the genus Caloramator.…”
mentioning
confidence: 99%
“…Vanadium(V)-reduction was inferred when the colourless medium changed to green and/or a green precipitate was formed. Vanadium(V)-reduction was confirmed using the vanadate assay as described by Carpentier et al (2003). For this, 250 ml 1 % (w/v) diphenylcarbazide in acetone was added to 250 ml 2 M H 2 SO 4 and 500 ml diluted sample was added.…”
mentioning
confidence: 99%